PEMBUATAN YOGHURT BUAH NAGA MERAH (Hylocereus polyrhizus L.): PROPORSI SARI BUAH DAN SUSU UHT TERHADAP VIABILITAS BAKTERI DAN KEASAMAN YOGHURT - Teguh, Ryanbakti Pranata Kusuma; Nugerahani, Ira; Kusumawati, Netty (Widya Mandala Surabaya Catholic University, 2015)
Red dragon fruit in yoghurt may incrase fermentation rate. This reasearch was to determine the influence of the proportion of red dragon fruit juice and UHT milk on viability of bacteria and yoghurt acidity. The experimental design used Randomized Block Design (RBD) with single factors, proportion of fresh juice and UHT milk 0:100 (M0), 5:95 (M1), 10:90 (M2), 15:85 (M3) 20:80 (M4) 25:75 (M5). The analyzed parameters were viability of bacteria, pH, and acidity of yoghurt. Obtained data statistically analyzed by ANOVA (Analysis of Varians) at Î± = 5%. If there was a significant difference, then it continued by DMRT (Duncan's Multiple Range Test) test to determine which level of proportion that gives significant differences. The difference in the proportion of red dragon fruit juice and UHT milk was significantly effect to the viability of bacteria, pH and total acid of yoghurt. The higher proportion of red dragon fruit juice increased viability of bacteria and total acid while pH decreased. Based on research, lactic acid bacteria ranged between 9,4624-10,9345 log cfu/m, pH ranged between 4,367-4,806; and total acid ranged between 24,33-48,33 oSH.